Branding Strategy for Building Institution Image: Study on Madrasah Aliyah Islamiyah Senori Tuban - Chala, Ni'mal; Sujianto, Agus Eko; Sulistyorini, Sulistyorini (Journal of Education Method and Learning Strategy, 2025)
Fierce competition in the education sector requires madrasas to build a positive image of madrasas through effective branding strategies in increasing public trust. As an educational institution Madrasah Aliyah Al Islamiyah Senori Tuban Regency plays an important role in introducing and promoting the name of the madrasah. Madrasah Aliyah Al Islamiyah Senori Tuban Regency implements a branding strategy to improve the image of the institution. This study uses a qualitative approach with a field study approach. The research method uses observation, documentation, and in-depth interviews. Miles and Huberman's interactive analysis is used for data analysis, which includes data condensation activities, data appearance, drawing conclusions, or data verification. The results of this study show that (1) MAIS builds a branding strategy in improving the image of the institution through cost, differentiation, and focus leadership strategies. (2) supporting factors in building branding in improving the image of the MAI Senori institution include management commitment, academic and non-academic achievements, and community support. (3) The inhibiting factor is the limitation of modern facilities and teaching staff with digital competence.